Autobiography of My Hungers - González, Rigoberto (The University of Wisconsin Press, 2013)
In the second of his trio of acclaimed memoirs, Rigoberto González looks at his past through a startling lens: hunger. A childhood of neglect, adolescent yearnings, and adult desire for a larger world, another lover, a different body-all are explored by González in a series of heartbreaking and poetic vignettes.